2022
DOI: 10.3389/fnmol.2022.1034766
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome assembly protein 1-like 5 alleviates Alzheimer’s disease-like pathological characteristics in a cell model

Abstract: Alzheimer’s disease (AD) remains one of the most common dementias of neurodegenerative disease-related diseases. Nucleosome assembly protein 1-like 5 (NAP1L5) belongs to the NAP1L protein family, which acts as a histone chaperone. However, the function and mechanism of NAP1L5 in AD are still unclear. Bioinformatics analysis, RT-qPCR, and Western blotting results showed that NAP1L5 was downregulated in the brain tissues of AD patients and a mouse cell model of AD. NAP1L5 overexpression alleviated (Amyloid-β pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…38 NAP1L5 is a nucleosome assembly protein that is involved in regulating chromatin structure and gene expression. 25 The study by Zhao and colleagues examined the function of NAP1L5 in hepatocellular carcinoma (HCC), and low expression of NAP1L5 was found in HCC, and its downregulation was associated with shorter survival and disease-free survival. 39 In addition, the study found that NAP1L5 inhibits the PI3K/AKT/mTOR signaling pathway in HCC by regulating MYH9, suggesting that NAP1L5 may be a potential target.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…38 NAP1L5 is a nucleosome assembly protein that is involved in regulating chromatin structure and gene expression. 25 The study by Zhao and colleagues examined the function of NAP1L5 in hepatocellular carcinoma (HCC), and low expression of NAP1L5 was found in HCC, and its downregulation was associated with shorter survival and disease-free survival. 39 In addition, the study found that NAP1L5 inhibits the PI3K/AKT/mTOR signaling pathway in HCC by regulating MYH9, suggesting that NAP1L5 may be a potential target.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that stable expression of HOXD8 inhibits cell proliferation, anchorage‐independent growth, and invasion, and can induce apoptotic events in CRC cells by upregulating executioner caspases 6 and 7 and cleaved PARP 38 . NAP1L5 is a nucleosome assembly protein that is involved in regulating chromatin structure and gene expression 25 . The study by Zhao and colleagues examined the function of NAP1L5 in hepatocellular carcinoma (HCC), and low expression of NAP1L5 was found in HCC, and its downregulation was associated with shorter survival and disease‐free survival 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation